Cross-border evidence gathering: equality of arms within the EU? - van Wijk, M.C. (Utrecht University, 2017)
The European Union (EU) has set the objective to develop an Area of Freedom, Security and Justice, in which on the one hand freedom of movement is promoted and on the other hand a high level of security is ensured. The EU is therefore adopting measures to enhance international cooperation in criminal matters among the police and judicial authorities of its Member States. The adopted instruments concerning evidentiary matters, such as the gathering, freezing and/or confiscation of information and materials in another EU Member State, seem to serve the main purpose of assisting the authorities in investigating and prosecuting (cross-border) crime. This raises the question to what extent the defence is also given the possibility to gather – or to have gathered – information and materials in another EU Member State with the aim of preparing and presenting its case at trial and, in particular, whether the current (EU) legal framework on cross-border evidence gathering meets the requirements of the principle of equality of arms. This thesis addresses this question by, first of all, discussing the concept of equality of arms, as enshrined in both Article 6 ECHR and Article 47 CFR. It explains to what extent this principle is applicable to cross-border or transnational criminal proceedings and whether it has an autonomous meaning within the EU. In addition, it discusses which requirements can be deduced from the principle in relation to the possibilities of the defence to gather evidence in another EU Member State to prepare and presents its case. Subsequently, the focus is on the development of the European legislation – from both the Council of Europe and the EU – regulating the procedure of cross-border evidence gathering over the last decades. The aim is to explain the position of the defence in this development and to what extent the European legislation gives opportunities to the defence to request the assistance of foreign authorities in obtaining specific information and materials in another EU Member State. In order to understand how the European legislation is applied in practice by the EU Member States, this thesis includes a comparative study of three national jurisdictions: the Netherlands, England and Wales, and Italy. These three jurisdictions each represent a different criminal justice system, either more inquisitorial or adversarial in nature. The comparative study describes how a chosen jurisdiction interprets the principle of equality of arms. Furthermore, it examines to what extent the national jurisdiction allows the defence to carry out independent investigations abroad and how it gives the defence the opportunity to trigger the mechanism of international cooperation and to participate in the requested investigation. Finally, this thesis also includes an analysis of the criminal justice system of the International Criminal Court. In this system evidence gathering depends most of the time on State cooperation and both the Prosecutor and the defence are allowed to conduct independent investigations and seek the assistance of States. It is therefore used as a source of inspiration for potential changes of the EU legislation on cross-border evidence gathering.
Keywords: Equality of arms; AFSJ; international cooperation; evidence; defence investigations; ICC; SDG 16 - Peace, Justice and Strong Institutions